Contested Spaces. Meaningful Places. Contemporary Performances of Place and Belonging in Spain and Brazil - Maria J. C. Krom (Journal of Ethnology and Folkloristics)
This essay aims to contribute to current anthropological debate on space and place, analysing in two instances of festival performance how, on the one hand the politics of appropriation of space contributes to the configuration of power relations, and how on the other hand, participants in these festivals engage individually and collectively with physical space(s) to create places which they experience as meaningful in terms of identity and belonging.